Contraction Transients of Skinned Muscle Fibers - Podolsky, R. J. (1974)
The contraction kinetics of calcium-activated skinned muscle fibers were studied after step decreases in load by means of a quickly responding recording system. The steady velocity at a given relative load was close to that found in electrically stimulated, intact muscle fibers. The presteady motion had the same shape as that of intact fibers, but the time scale of the transient was nearly two times slower. The duration of the initial phase of the motion, where the velocity was greater than the steady value, and the time at which the subsequent low velocity phase ended, were both stretched out to the same extent. Changing the temperature had the same effect on the length of these two phases of the transient. The results indicate that both phases of the transient are produced by the same underlying factors and can be taken as evidence that the entire transient originates in the crossbridge mechanism. In this case the experimental technique described here provides a basis for distinguishing between chemical parameters that affect contractility by (a) controlling the number of sites at which crossbridges can be formed, as opposed to (b) changing the kinetic properties of a given number of sites.